2014
DOI: 10.1016/j.str.2013.12.003
|View full text |Cite
|
Sign up to set email alerts
|

A Structure-Based Model of Substrate Discrimination by a Noncanonical PDZ Tandem in the Intramembrane-Cleaving Protease RseP

Abstract: During the extracytoplasmic stress response in Escherichia coli, the intramembrane protease RseP cleaves the anti-σ(E) protein RseA only after the membrane-anchored protease DegS truncates the periplasmic part of RseA that suppresses the action of RseP. Here we analyzed the three-dimensional structure of the two tandemly arranged PSD-95/Dlg/ZO-1 (PDZ) domains (PDZ tandem) present in the periplasmic region of RseP and revealed that the two putative ligand-binding grooves constitute a single pocket-like structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(82 citation statements)
references
References 31 publications
(55 reference statements)
3
78
1
Order By: Relevance
“…Ironically, similar to nicastrin, the PDZ domains of RseP were originally proposed to be involved in substrate binding (62). This was later ruled out after they were shown to be dispensable for catalysis, and high-resolution structures of the PDZ domains demonstrated that the putative substrate-binding pocket is both too narrow to accommodate substrate and physically covered by a helix (62,63).…”
Section: Discussionmentioning
confidence: 99%
“…Ironically, similar to nicastrin, the PDZ domains of RseP were originally proposed to be involved in substrate binding (62). This was later ruled out after they were shown to be dispensable for catalysis, and high-resolution structures of the PDZ domains demonstrated that the putative substrate-binding pocket is both too narrow to accommodate substrate and physically covered by a helix (62,63).…”
Section: Discussionmentioning
confidence: 99%
“…The periplasmic PDZ domain is specific for regulated processing of RseA after truncation by DegS. Removal of the PDZ domain led to intramembrane cleavage of RseA (Hizukuri et al, 2014), suggesting that this domain is not required for processing of lipoprotein signal peptides. Lsp proteins from firmicutes can complement an lsp temperature sensitive mutant of E. coli, suggesting that the enzymes are functionally conserved as seen for Lgt (Pragai et al, 1997); however, kinetic analyses have not yet been performed to determine specificity and mechanism of the reaction.…”
Section: Prolipoprotein Signal Peptidase (Lsp)mentioning
confidence: 99%
“…The PDZ ( P ost synaptic density protein, D rosophila disc large tumor suppressor, Z onula occludens-1 protein) (Hizukuri et al, 2014) domain, consisting of five to six β-strands and two to three α-helices, typically recognizes a few amino acid residues at the C-termini of target proteins. The DegS and RseP proteases, which function in the regulatory cascade controlling the activation of the alternative sigma factor σ E (see below), contain PDZ domains that regulate their proteolytic activity, thus controlling the subsequent expression of downstream genes in response to extracytoplasmic stress and the associated accumulation of unfolded outer membrane proteins (Walsh et al, 2003; Hasselblatt et al, 2007; Hizukuri et al, 2014). PAS ( P er A rnt S im) and GAF (c G MP-specific phophodiesterases, A denylyl cyclases and F hlA) domains, with their characteristic α/β folds, sense signals as diverse as O 2 , metabolites and redox potential.…”
Section: Bacterial Sensing Motifsmentioning
confidence: 99%
“…Specific activation of extracytoplasmic sigma factors such as σ E in enterobacteria or σ K in mycobacteria is controlled with a high degree of precision provided by sequential proteolysis of the cognate anti-sigma factor by intracytoplasmic membrane S1P (site one) and S2P (site two) proteases. Tandem PDZ domains in the S2P protease RseP act as a filter to prevent cleavage of large periplasmic domains (Hizukuri et al, 2014). Unfolded outer membrane proteins activate proteolysis of the RseA periplasmic domain by the S1P RseS.…”
Section: Signal Discriminationmentioning
confidence: 99%